The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1038/s41598-022-18739-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the temporal discrimination threshold in musician’s dystonia

Abstract: The temporal discrimination threshold (TDT) has been established as a biomarker of impaired temporal processing and endophenotype in various forms of focal dystonia patients, such as cervical dystonia, writer’s cramp or blepharospasm. The role of TDT in musician’s dystonia (MD) in contrast is less clear with preceding studies reporting inconclusive results. We therefore compared TDT between MD patients, healthy musicians and non-musician controls using a previously described visual, tactile, and visual-tactile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Although Musician’s dystonia is a disorder in which dexterity is impaired primarily during the performance of specific tasks, it is known that there are differences in hand perceptive or sensory-motor functions unrelated to specific motor tasks, such as longer temporal discrimination threshold (TDT), compared to healthy individuals ( 18 , 19 ). Conversely, it has been reported that TDT is not altered in musicians with dystonia ( 20 ). Furthermore, biomechanical factors seem to be related to musicians with dystonia, at least in a subgroup ( 11 , 21 ).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Although Musician’s dystonia is a disorder in which dexterity is impaired primarily during the performance of specific tasks, it is known that there are differences in hand perceptive or sensory-motor functions unrelated to specific motor tasks, such as longer temporal discrimination threshold (TDT), compared to healthy individuals ( 18 , 19 ). Conversely, it has been reported that TDT is not altered in musicians with dystonia ( 20 ). Furthermore, biomechanical factors seem to be related to musicians with dystonia, at least in a subgroup ( 11 , 21 ).…”
Section: Methodsmentioning
confidence: 92%
“…TOJT of the participants was defined as the time interval at which the correction rate exceeded 75% ( Supplementary Figure 1-3 ). We opted for mechanical stimulation instead of electrical stimulation for simplicity, while adhering to the target body parts of previous studies that measure TDT of patients with MD ( 20 ). Prior to measurements, we ensured that the magnitude of the mechanical stimuli was sufficiently above each participant’s tactile threshold.…”
Section: Methodsmentioning
confidence: 99%